R and Quantitative Data Analysis. - Webb, Paul (Social Research Update)
The article focuses on the application of R in getting into grips with having expended effort rewarded by its power and ability to work in a seamless manner. It has been considered a powerful and free statistical environment in the language programming. The author has noted that though the R learning curve might be steep due to R driven from console, there is a possibility to work with it through the use of R commander. This interface is expected to be more intuitive for users even without the experience driven applications of command line.